2015
DOI: 10.1155/2015/519638
|View full text |Cite
|
Sign up to set email alerts
|

Increased Serum Interleukin-9 Levels in Rheumatoid Arthritis and Systemic Lupus Erythematosus: Pathogenic Role or Just an Epiphenomenon?

Abstract: The purpose of this paper was to evaluate the levels of IL-9 in patients with SLE and RA compared with controls and the association of IL-9 levels with clinical and laboratory parameters. IL-9 levels were assessed in 117 SLE patients, 67 RA patients, and 24 healthy controls by ELISA. Clinical and laboratory parameters were recorded. The IL-9 serum levels were significantly higher in RA patients (4,77 ± 3,618 pg/mL) and in SLE patients (12,26 ± 25,235 pg/mL) than in healthy individuals (1,22 ± 0,706 pg/mL) (p <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 44 publications
0
28
0
1
Order By: Relevance
“…Regarding repercussions of the Th9 response, studies on rheumatoid arthritis and systemic lupus erythematosus have shown that the cell produces large amounts of IL-9 that intensify the inflammatory process 16 17. In allergic diseases, Th9 cells producing IL-9 induce mechanisms that culminate in the increased production of IgE and mast cell degranulation 14 18.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding repercussions of the Th9 response, studies on rheumatoid arthritis and systemic lupus erythematosus have shown that the cell produces large amounts of IL-9 that intensify the inflammatory process 16 17. In allergic diseases, Th9 cells producing IL-9 induce mechanisms that culminate in the increased production of IgE and mast cell degranulation 14 18.…”
Section: Introductionmentioning
confidence: 99%
“…erythematosus [33], rheumatoid arthritis [34,35] and systemic sclerosis [36] but their clinical significance are still not completely understood. It has been debated if IL-9 has a role in the pathogenesis of these diseases, or if its presence is due to an epiphenomenon caused by a broad activation of inflammatory mechanisms, and this has made it difficult to define its function in the development of the disease; thus further studies are required to elucidate the pathogenic role in those rheumatic disease [37,38].…”
Section: Autoimmune Diseasesmentioning
confidence: 99%
“…IL-9 has been demonstrated to be increased significantly in the sera of RA patients not related to disease duration, disease activity score (DAS28), health assessment questionnaire (HAQ), rheumatoid factor positivity or erosions on radiography [25]. High levels of IL-9 have been also detected in patients' first-degree relatives' sera with RA or with asymptomatic RA-related autoimmunity [26,33].…”
Section: Il-9 and Th9 Cells In Ramentioning
confidence: 99%
“…This paper aims to review the evidence indicating that Th9 cells may contribute to the pathogenesis of autoimmune-related diseases, due to the recent demonstration of a possible role of Th9 T cells and of their related cytokine IL-9 in rheumatoid arthritis (RA), psoriatic arthritis (PsA), systemic vasculitis, systemic lupus erythematosus (SLE) and systemic sclerosis (SSc) [20][21][22][23][24][25][26][27][28] (Fig. 1 shows the possible tissue target of Th9-mediated inflammation).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation